Exploring the Impact of a Dual Occupancy Neonatal Intensive Care Unit on Staff Workflow, Activity, and Their Perceptions. (April 2019) - Broom, Margaret; Kecskes, Zsuzsoka; Kildea, Sue; Gardner, Anne
In 2012, a tertiary neonatal intensive care unit (NICU) transitioned from an open plan (OP) to a dual occupancy (DO) NICU. The DO design aimed to provide a developmental appropriate, family-centered environment for neonates and their families. During planning, staff questioned the impact DO would have on staff workflow and activity. To explore the impact of changing from an OP to a DO NICU, a prospective longitudinal study was undertaken from 2011 to 2014, using observational, time and motion, and surveys methods. Main outcome measures included distance walked by staff, minutes of staff activity, and staff perceptions of the DO design. Results highlighted no significant difference in the distances clinical nurses walked nor time spent providing direct clinical care, whereas technical support staff walked further than other staff in both designs. Staff perceived the DO design created a developmentally appropriate, family-centered environment that facilitated communication and collaboration between staff and families. Staff described the main challenges of the DO design such as effective staff communication, gaining educational opportunities, and the isolation of staff and families compared to the OP design. Our study provides new evidence that DO provides an improved developmentally environment and has similar positive benefits to single-family room for neonates and families. Such design may reduce the larger floor plan's impact on staff walking distance and work practices. Challenges of staff transition can be minimized by planning and leadership throughout the development and move to a new design.